Institutionalization of Alternative Dispute Resolution (ADR) in Indonesia to facing ASEAN Economic Community (AEC) - Yessy Meryantika Sari (Universitas Muhammadiyah Metro, 2017)
Alternative dispute resolution can be one option the parties to resolve business disputes when the settlement of disputes through the courts used are considered less advantageous for businesses and consumers alike. Although there is still a shortage of the power of law and legal compliance agreements and the development of professional arbitration institution. This paper analyzes the institutionalization of ADR in Indonesia as ASEAN countries member and how readiness Indonesian National Board of Arbitration to facing AEC. A basic distinction is drawn regulation in Indonesia. The method used in this paper is a descriptive analyzis normative legal method. In this case the author uses literature study from a legal perspective and regulatory in Indonesia. This paper discusses the development of institutional ADR, which includes institutional ADR in indigenous people in Indonesia, the institutionalization of ADR outside the court and the institutionalization of ADR in courts as well as the readiness of BANI as an independent agency that provides alternative dispute resolution services.